Determinants of Attractiveness of the Sacred Area of Pakkwarue Wells - Andi Muh Rusdi Maidin; Rajamemang Rajamemang; Wahyudi Putera Yudhie; Wahyuti Wahyuti; Andi Tenri Ulmi; Indah Lestari Yahya (Universitas Dharma Wacana, 2022)
Sacred Area: The